Antibacterial potential of cassava (manihot esculenta) crude aqueous leaf extract against Escherichia coli, Pseudomonas aeruginosa and staphylococaus aureus. - Calambuhay, Sanie Karl (UPHSI, 2005)
Manihot esculenta, commonly known as cassava, is an important lowland crop of the tropics. Its use is mainly as a food source but it could also be a folk remedy for illnesses such as tumors, other cancerous infections and marasmus. It was found to contain cyanogenic glucosides, linamarin, and lotaustralin which contain potentially toxic levels of hydrocyanic acid. These bioactive components are most concentrated in the young leave. Since bioactivity or toxicity are the indicators of pharmacological potenial, this study was designed with the general objective of finding wheter cassava has anti-bacterial potetial against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The specific objectives are to find what dillution of cassava crude aqueous leaf extract is most inhibiting on the growth of each of the three bacterial strains and to determine which of the three bacterial strains is most inhibited. Cassava leaves were cut, osterized, and subjected to manual compressor. Nine treatments were preapared with three replicates each. The pure extracts (100%), the six dilutions of 80%, 60%, 40%, 30%, 20%, and 10%, the positive control (Gentamicin) and the negative control (distilled water) constituted the nine treatments laid out in a completely randomized design. The Kirby-Bauer Disc Diffusion Method was used as the antimicrobial susceptibility test. The diamters of the zones of inhibition were measured using a Vernier caliper. It was found that cassava has antibacterial potential with teh formation of zones of inhibition. This may be due to the presence of hydrocyanic acid. Using the one-way ANOVA and DMRT, it was found that 100% and 30% cassava leaf extract has manifested significantly higher inhibiting potential against both E. coli and S. aureus. Staphyloccocus aureus was the most inhibited bacterium since all dilutions formed zones of inhibition. This may be due to its sensitivity to unsaturated fatty acids in plants.